Networking as a socio-psychological resource of resilience and overcoming uncertainty in entrepreneurs - A.I. Kulikova; M.Y. Sachkova (Современная зарубежная психология)
Context and relevance. Entrepreneurship is a professional activity associated with high risk, uncertainty, responsibility and competition. The challenges of entrepreneurship are exacerbated by the peculiarities of today's unstable world, which makes it really important to find resources to deal with the difficulties that come up in professional life. Networking has been shown to be an important part of the business system, but its potential as a social and psychological resource has not yet been fully explored. The aim of this study is to review research on networking and entrepreneurial resilience. The results obtained in the study suggest that networking can be a resource for overcoming uncertainty and increasing resilience among entrepreneurs. The main types of difficulties faced by entrepreneurs are presented. The identified links between networking and resilience and overcoming uncertainty among male and female entrepreneurs are described. Methods and materials. Systematic search, content and bibliometric analysis in international scientometric databases on the research topic. Conclusions. As a result of a theoretical review and analysis of data presented in contemporary foreign studies, it has been established that networking helps entrepreneurs cope with stress and uncertainty through mentoring, cooperation, market information, emotional support, and increased self-confidence